Nasal CPAP and preterm bradycardia: cause or cure. (23rd May 2014) - MacLaren, Andrew Torrance; Peters, Colin; MacDonald, Peter D
Abstract : Nasal continuous positive airway pressure (nCPAP) is widely used for the treatment of respiratory distress syndrome and apnoea of prematurity. Complications related to fixation devices have been well documented. We report a clinically well preterm baby suffering intermittent, profound episodes of bradycardia without any prior associated apnoea or desaturation. We believe these episodes were due to the oculocardiac reflex related to orbital compression from the continuous positive airway pressure (CPAP) fixation straps. Bradycardia was replicated by gentle ocular compression and the episodes resolved after repositioning the CPAP straps. Vagal overstimulation has previously been reported in preterm babies but we believe this to be the first case in which pressure from CPAP strapping has been reported to trigger bradycardia. However, we suspect that similar cases could easily go unrecognised. Careful positioning of CPAP securing straps may prevent accidental vagal overstimulation contributing to episodic bradycardia.